CLINICAL CHARACTERISTIC OF COVID-19 IN ELDERLY AND MIDDLE-AGE ADULT IN DR MOHAMMAD SOEWANDHI GENERAL HOSPITAL - Yudita Wulandari; Vincentius Diamantino Supit; Henry Asaleo; Regita Marentek; Jansen Irawan; Rio Tritanto; Richard Hartanto; Steven Hermantoputra Halim (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: The different characteristics of the elderly and young people may provide different characteristics of COVID-19. This research aim is to provide information on the characteristics of COVID-19 patients, especially elderly patients. Aim: To analyzed comparisson of clinical characteristic COVID-19 in elderly and young age patients. Method: This study is a retrospective observational study with a cross-sectional approach in COVID-19 patients hospitalized at Soewandi General Hospital from May 1st 2020 until November 31th 2020. This study compared the characteristics of COVID-19 patients at elderly and young ages. Result: There were 368 COVID-19 patients with 95 elderly patients (25.81%) and 273 young patients (74.19%). The most frequent symptoms experienced by elderly patients in sequence are cough, gastrointestinal disturbances, fever, and fatigue. It was found that the proportion of COVID-19 patients with comorbid diabetes mellitus (DM) and hypertension (HT) was higher in elderly patients than in younger patients (p